RUPTURE DIAPHRAGMATIQUE RÉVÉLÉE PAR UN ÉTRANGLEMENT INTRA-THORACIQUE DE L’ESTOMAC - Kaimba Bray Madoué; Edzimbi Anne Laure; Akouya Seid Dounia; Hervé Pierre (European Scientific Journal, ESJ, 2015)
Introduction: Undiagnosed left sided traumatic diaphragmatic rupture can be revealed by complications such as occlusion. Clinical case: We reported a case of traumatic diaphragmatic hernia revealed by gastric strangulation in a 42 years old patient, victim of a left hemi thorax penetrating injury six months before. The diagnosis suspected on a chest x-ray showing left hemi thoracic air-fluid level was confirmed by thoracoabdominal CT-scan. On surgical exploration we found a diaphragmatic rupture with stomach and greater omentum strangulation. The surgery consisted of reduction of herniated organs with closing of the diaphragmatic defect. Surgical outcome was simple. Conclusions: Occlusion as mode of revelation of diaphragmatic rupture is rare. Its rapid surgical management provides a favorable outcome.